Outcome and prognostic factors in single brain metastases from small-cell lung cancer - Bernhardt, Denise; Adeberg, Sebastian; Bozorgmehr, Farastuk; Opfermann, Nils; Hörner-Rieber, Juliane; König, Laila; Kappes, Jutta; Thomas, Michael; Unterberg, Andreas; Herth, Felix; Heußel, Claus Peter; Warth, Arne; et al. (Strahlentherapie und Onkologie, 2018)
PurposeWhole brain radiation therapy (WBRT) is historically the standard of care for patients with brain metastases (BM) from small-cell lung cancer (SCLC), although locally ablative treatments are the standard of care for patients with 1-4 BM from other solid tumors. The objective of this analysis was to find prognostic factors influencing overall survival (OS) and intracranial progression-free survival (iPFS) in SCLC patients with single BM (SBM) treated with WBRT.MethodsA total of 52 patients were identified in the authors’ cancer center database with histologically confirmed SCLC and contrast-enhanced magnet resonance imaging (MRI) or computed tomography (CT), which confirmed SBM between 2006 and 2015 and were therefore treated with WBRT. A Kaplan-Meier survival analysis was performed for OS analyses. The log-rank (Mantel-Cox) test was used to compare survival curves. Univariate Cox proportional-hazards ratios (HRs) were used to assess the influence of cofactors on OS and iPFS.ResultsThe median OS after WBRT was 5 months and the median iPFS after WBRT 16 months. Patients that received surgery prior to WBRT had a significantly longer median OS of 19 months compared to 5 months in the group receiving only WBRT (p = 0.03; HR 2.24; 95% confidence interval [CI] 1.06-4.73). Patients with synchronous disease had a significantly longer OS compared to patients with metachronous BM (6 months vs. 3 months, p = 0.005; HR 0.27; 95% CI 0.11-0.68). Univariate analysis for OS revealed a statistically significant effect for metachronous disease (HR 2.25; 95% CI 1.14-4.46; p = 0.019), initial response to first-line chemotherapy (HR 0.58; 95% CI 0.35-0.97; p = 0.04), and surgical resection (HR 0.36; 95% CI 0.15-0.88; p = 0.026). OS was significantly affected by metachronous disease in multivariate analysis (HR 2.20; 95% CI 1.09-4.45; p = 0.028).ConclusionsUnivariate analysis revealed that surgery followed by WBRT can improve OS in patients with SBM in SCLC. Furthermore, synchronous disease and response to initial chemotherapy appeared to be major prognostic factors. Multivariate analysis revealed metachronous disease as a significantly negative prognostic factor on OS. The value of WBRT, stereotactic radiosurgery (SRS), or surgery alone or in combination for patients with a limited number of BM in SCLC should be evaluated in further prospective clinical trials.
Gesehen am 24.05.2018
Published online: 30 October 2017